AB0198 Differential characteristics of patients discontinuating several biological therapies in a cohort of rheumatoid arthritis patients. (15th June 2017) - Tornero, C; Plasencia, C; Pascual-Salcedo, D; Hernández, B; González, M; Bonilla, MG; Nuño, L; Villalba, A; Peiteado, D; Bogas, P; Moral, E; Balsa, A
Abstract : Background: The treatment of Rheumatoid Arthritis (RA) has been transformed in the last decade with the introduction of biologic therapy. Nevertheless, a substantial proportion of patients (pts) are found to be primary or secondary nonresponders and will receive several biologics during the course of the disease. Evidence is lacking on the characterization of patients failing several agents and those who have adequate clinical response to their first biological treatment. Objectives: To compare demographic, clinical and analytical characteristics in a cohort of RA pts who have failed treatment with at least two biological agents ("switchers") and another cohort of RA patients showing a sustained clinical good response to their first therapy ("maintainers"). As a secondary objective, reasons for therapy discontinuation were also evaluated. Methods: A total of 186 patients under biological therapy of the RA-PAZ cohort were included in this observational study. In this cohort, 63 pts were switchers and 123, maintainers. Baseline demographic data and clinical disease activity (DAS 28 -ESR), clinical improvement (delta-DAS 28) and serological data (CRP and ESR) were evaluated at baseline and sixth months after starting the first biological treatment.Serum anti-drug antibodies (ADA) were measured by bridging ELISA at the last visit available during the follow-up period under the first treatment. Reasons for discontinuation of the first therapy and the number of biologic treatments received during the course of the disease were also evaluated. Results: Demographic and clinical characteristics of both groups are shown in Table 1 .Mean Age (49, 96±10, 82 vs 53, 77±12, 91, p=0, 046) and disease duration (6, 79±6, 19 vs 9, 97±8, 56, p=0, 001) prior to biologic therapy initiation were lower in the switchers.Furthermore, a higher proportion of switchers had extraarticular manifestations in comparison to the maintainers (18/63 (28, 6%) vs 16/121 (13, 2%), p=0, 016). Clinical activity at baseline (DAS28: 5, 74±1, 26 vs 5, 01±1, 14, p=0, 01) and after 6 months of starting the first biological therapy (DAS28: 4, 45±1, 6 vs 3, 22±1, 1, p=0, 001) were statistically significant higher in the switchers. At the last visit under the first biologic, there were also more ADA-positive pts in the switchers (6/25 (24%) vs 1/73 (1, 4%), p=0, 01).Moreover, duration under biologic treatment was higher in this group. In terms of the reason for discontinuation of the first biologic, 22, 2% of pts showed primary lack of efficacy;38, 1%, secondary loss of efficacy; 33, 3%, adverse effects;4, 8%interrupted because of other reasons and 1, 6% because of remission. There was no association between reasons for discontinuation of the first therapy because of primary or secondary failure and adverse effects (3, 4±0, 9 vs 3, 75±1, 11vs 3, 86±1, 3, p=0, 6) with the number of treatments received. Conclusions: In our biologic therapy RA-PAZ cohort, we found a subgroup of younger pts, with a more systemic phenotype of the disease and a higher disease activity, who required a prompter biological therapy initiation. This subgroup of pts is more susceptible to biological treatment failures. The development of ADA after the first biological agent was also associated with the need to use more biologics. Disclosure of Interest: None declared